A Conversation about History, Race, Immigration, and the City on a Hill. Issue 3 (3rd July 2021) - Rowley, Matthew; Van Engen, Abram
Abstract : This contribution is a conversation between Matthew Rowley and Abram Van Engen about the latter's recent City on a Hill: A History of American Exceptionalism (Yale University Press, 2020). They discuss the changing importance of the Pilgrims and Puritans over four centuries, looking in particular at the contested nature of American identity that was constructed on divergent national foundation narratives. The conversation spans from the Mayflower in 1620 to debates over celebrating and confronting history in the present. We also discuss changing views of history, race, immigration, nationalism, and American exceptionalism, all in the context of political and historical polarization.